Museums, archives and protest memory - Chidgey, Red; Garde-Hansen, Joanne 1975- (Palgrave Macmillan, 2024)
This book addresses the emergence of ‘protest memory’ as a powerful contemporary shaper of ideas and practices in culture, media and heritage domains. Directly focused on the role of museum and archive practitioners in protest memory curation, it makes a compelling contribution to our understanding of how social movements and activist experiences are publicly remembered and activated for social and environmental justice.
Keywords: Memory Studies; Cultural Heritage; Collective memory; Cultural property; Protest; Aktivismus; Museum; Archiv; Kulturerbe